Reshaping Social Life - Irwin, Sarah (Taylor & Francis, 2005)
Caught up in current social changes, we do not fully understand the reshaping of social life. In sociological analyses there is a conceptual gap between subjectivities and social structural processes, and we face real difficulties in understanding social change and diversity. Through analysis of key areas of social life, here, Sarah Irwin develops a new and exciting resource for better understanding our changing social world. Breaking with conventional approaches and reconnecting the subjective with the objective, Irwin's book develops a new conceptual and analytical perspective with social relationality, interdependence and social context at its heart. The new perspective is developed through grounded analyses of empirical evidence, and draws on new data. It explores and analyzes: * significant changes in family forms, fertility, gender relations and commitments to employment, children and care, both now, and with comparisons to early twentieth century developments * the meshing of norms and social relations in contexts of change * diverse values, norms and perceptions of fairness, analyzed with respect to diversity over the life course, and in respect of gender, ethnicity and social class. Through analysis of context, Irwin offers new insights, and tackles puzzles of explanation. Reshaping Social Life offers a fascinating and innovative way of slicing into and re-interrogating our changing social world, and is sure to become a landmark resource for students, scholars and researchers.